Donor Spins in Silicon for Quantum Technologies. Issue 11 (24th July 2020) - Morello, Andrea; Pla, Jarryd J.; Bertet, Patrice; Jamieson, David N.
Abstract: Dopant atoms are ubiquitous in semiconductor technologies, providing the tailored electronic properties that underpin the modern digital information era. Harnessing the quantum nature of these atomic‐scale objects represents a new and exciting technological revolution. In this article, the use of ion‐implanted donor spins in silicon for quantum technologies is described. It is reviewed how to fabricate and operate single‐atom spin qubits in silicon, obtaining some of the most coherent solid‐state qubits, and pathways to scale up these qubits to build large quantum processors are discussed. Heavier group‐V donors with large nuclear spins display electric quadrupole couplings that enable nuclear electric resonance, quantum chaos, and strain sensing. Donor ensembles can be coupled to microwave cavities to develop hybrid quantum Turing machines. Counted, deterministic implantation of single donors, combined with novel methods for precision placement, will allow the integration of individual donor spins with industry‐standard silicon fabrication processes, making implanted donors a prime physical platform for the second quantum revolution. Abstract : Donor atoms in silicon are among the most coherent quantum systems in the solid state, and can be integrated with industry‐standard manufacturing methods. This review and perspective article describes applications of single donors in quantum computing, sensing and chaos, and donor ensembles for quantum memories. Scale‐up technologies based on deterministic single‐ion implantation are discussed, alongside strategies for coupling and operating large numbers of donor qubits.